Recent Progress on Interface Engineering for High‐Performance, Stable Perovskites Solar Cells. Issue 11 (27th April 2020) - Zhu, Yiyi; Poddar, Swapnadeep; Shu, Lei; Fu, Yu; Fan, Zhiyong
Abstract: Rapid progress in the domain of perovskite solar cells (PSCs) has boosted the power conversion efficiency (PCE) of such cells to 25.2%. However, the long‐term stability of a high‐performance PSCs is still the foremost concern that hinders its practical application. The interfaces are considered as the key part that determines the overall device performance and longevity. These interfaces include the intralayer grain boundaries (GBs) inside the perovskites, the interface between perovskites with electron/hole transport layer (ETL/HTL), and the interface of ETL/HTL with top/down contacts. To acquire a deep and detailed understanding of the impacts of interfacial properties, herein, a concise overview of recent interfacial engineering strategies with the aim of minimizing traps, promoting carrier extraction, and improving stability are summarized. Abstract : The interfaces determine the overall device performance and stability. These interfaces include the intralayer grain boundaries inside the perovskites, the interface between perovskites with electron/hole transport layer (ETL/HTL), and the interface of ETL/HTL with electrodes. With the aim of minimizing traps, promoting carrier extraction, and improving stability, herein, an overview of recent interfacial engineering strategies is provided.